Isocratic High Performance Liquid Chromatographic Method for Determination of Metoprolol and Its Metabolite in Human Urine - PRI ISWATI UTAMI; SUGIYANTO SUGIYANTO; SUDIBYO MARTONO; LUKMAN HAKIM (Fakultas Farmasi Universitas Pancasila, 2016)
An isocratic reversed phase high performance liquid chromatographic (HPLC) method has been developed for the determination of metoprolol (MET) and α-hydroxymetoprolol (α-OH MET) in human urine. Analytes were extracted using dichloromethane. The optimized separations were performed on a Purospher® STAR RP-18e LiChroCART® (250 x 4.6 mm, 5μm) HPLC column within 12 min by an isocratic elution with 25 mmol/L aqueous potassium dihydrogen phosphate buffer (pH 3.0) containing 15% (v/v) acetonitrile and 15% (v/v) methanol, and UV detection at 234 nm. The method was validated for linearity, accuracy, precision and specificity. The calibration curves for both analytes were linear over the range investigated (1.0-64.0 μg/mL) with correlation coefficients of 0.999. Relative standard deviation (RSD) values were below 2%. For all of the analytes, recoveries value from 98.36±1.68 to 101.32±1.36 % and the limits of detection for MET and α-OH MET were 0.22 and 0.14 μg/mL, respectively. The method developed has been demonstrated to be sensitive and reliable for the measurement of MET and α-OH MET simultaneously in human urine.